Pocket companion to Robbins pathologic basis of disease. (Saunders, 1999)
This guide to Robbins Pathologic Basis of Disease, 4/e is liberally annoted with page references to facilitate cross referral. A handy pocket reference containing the essential skeletal elements found in parent book. Informs students what is important.